Energy stress-induced lncRNA HAND2-AS1 represses HIF1α-mediated energy metabolism and inhibits osteosarcoma progression - Kang, Yao (Am J Cancer Res, 2018)
During recent years, long noncoding RNAs (lncRNAs) have been recognized as key regulators in the development and progression of human cancers, however, their roles in osteosarcoma metabolism are still not well understood. The present study aims to investigate the expression profiles and potential modulation of specific lncRNA(s) in osteosarcoma metabolism. The high-throughput Hiseq sequencing was performed to screen for abnormally expressed lncRNAs in osteosarcoma cells cultured under glucose starvation condition, and lncRNA HAND2-AS1 was eventually identified as one that was significantly up-regulated when compared with normal cultured cells. Mechanistic investigations indicated that knockdown of HAND2-AS1 abrogated the energy stress-induced effect on cell apoptosis and proliferation, and promoted osteosarcoma progression. Moreover, knockdown of HAND2-AS1 promoted glucose uptake, lactate production, and the expression level of a serious of enzymes that involved in energy metabolism. Subsequently, RNA pull-down and RNA immuneprecipitation revealed that, upon energy stress, HAND2-AS1 regulated osteosarcoma metabolism through sequestering FBP1 from binding to HIF1α, thereby releasing HIF1α expression and promoting the protein level. Taken together, our integrated approach reveals a regulatory mechanism by lncRNA HAND2-AS1 to control energy metabolism and tumor development in osteosarcoma. Thus, HAND2-AS1 may be a potential biomarker and therapeutic target for the repression of osteosarcoma metabolism.